Enhancing Organizational Performance Through Strategic Planning and AI Integration: A Study on Predictive Analysis - Shafi, Muhammad Ammar; Ebrahim Mohammed, Mohammed Gamal; Rusiman, Mohd Saifullah; Mohamad Azmi, Nur Azia Hazida (Journal of Technology Management and Business, 2024)
This study explores the role of Artificial Intelligence (AI) in enhancing strategic planning and organizational performance in Abu Dhabi’s public sector. Despite AI’s potential benefits, research in this area, particularly in the public sector, has declined. A comprehensive survey using stratified and random sampling was conducted to gather insights into the perceived benefits, challenges, and resource constraints associated with AI adoption in Abu Dhabi’s public sector organizations. The findings, analyzed using SPSS, demonstrate that AI integration in strategic planning can significantly improve decision-making, efficiency, effectiveness, and public service delivery. This study provides valuable insights for policymakers and public sector managers, emphasizing the importance of AI in achieving long-term strategic goals and maintaining a competitive advantage. Future research should explore diverse contexts, specific AI applications, the integration of emerging technologies, comparative studies between organizations, and the ethical and societal implications of AI adoption to ensure responsible and effective use of AI in strategic planning.